HUBUNGAN KOMUNIKASI EFEKTIF ORANGTUA TENTANG PENDIDIKAN SEKS DENGAN PERILAKU SEKS BEBAS PADA REMAJA DI SMA KEMALA BHAYANGKARI 1 JAKARTA PADA BULAN JUNI TAHUN 2015 - Ratnawati, Diah; Rahmawati, Indah Lailliyah (Jurnal Keperawatan Widya Gantari Indonesia, 2015)
Sexuality cases were complicated problem for adolescent phase was phase when someone faced into several odds and problems both of development and environment that affected to sexuality practice of adolescent. This study was conducted to know relationship of parents “ communaction with sexual practive students SMA Kemala Bhayangkari 1”. This study was analytic descriptive quantitatif with cross sectional method, sample size were 150 responden. Analysis was by using Chi Square to analyze relantionship between child-parents” Communication with sexual practice that influenced by students SMA Kemala Bhayangkari 1 (old, gender and  knowledge) and parent characteristics (family type). The result by using univariane showed that 68 respondents  (45,3%) had negative sexual practice and 133 responden (88,7%) has good communication with their parent. Bivariate analysis showed that there were significant relationship between old (P = 0,000) gender (P = 0,017) knowledge (P = 0,007) and communication with parents (P = 0,001)  to sexual practice of student. Suggestion present to parents to promote friendly family condition so it shall be able to create open communication about reproductive health and sexuality